Sarapataanguna Pre- and Post-Islamic Philosophy as the Philosophy of the Traditional House of the Buton People of the Walaka - Muhammad Zakaria Umar (Universitas Islam Negeri Sunan Ampel Surabaya, 2017)
Since the issuance of the